Supramolecular hydrogels: synthesis, properties and their biomedical applications. (16th July 2015) - Dong, Ruijiao; Pang, Yan; Su, Yue; Zhu, Xinyuan
<x xml:space="preserve">Abstract</x> The recent progress in synthesis, properties and biomedical applications of supramolecular hydrogels has been reviewed.